Increased literacy of the best evidence base optimizes patient-clinician communication in convergent translational health care: Relevance for patient-centered modalities - Allen Khakshooy; Vandan Kasar; Melissa Nahcivan; Quyen Bach; Francesco Chiappelli (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dentistry in particular and biomedicine in general have undergone a fundamental transformation over the recent decades, which have been formalized by the Affordable Care Act, 2010. In brief, modern contemporary health care has evolved from procedure-driven and intervention-centered care based on research evidence to the administration and delivery of care that is patient-centered, effectiveness-focused, and that utilizes the best evidence base generated by systematic research synthesis (i.e., evidence-based). The present conceptualization of health care integrates translational research and translational effectiveness, and allows convergence of the multiple specialization fields of biomedicine (e.g., dentistry, internal medicine, and psychiatry) as well as the various medical traditions globally (i.e., Western, Ayurvedic, and Chinese medical traditions, etc.). The Hypothesis: Here, we propose the hypothesis that increased literacy of the best evidence base optimizes patient-clinician communication in the current convergent translational health care model including dental care. Evaluation of the Hypothesis: We discuss the salient points of this proposition, and outline the relevance of certain salient convergent patient-centered modalities of health care that intimately intertwine medicine and dentistry.